Using Optimization Models to Determine the Inventory Level in the Production Process - Szozda, Natalia; Tubis, Agnieszka (Wykorzystanie modeli optymalizacyjnych do wyznaczania poziomu zapasów w procesie produkcyjnym, 2011)
Growing requirements from customers concerning not only product quality but also time handling combined with pressure, cause managers to increasingly seek solutions that will allow them to optimize drawn up production plans. Logistic support to the production process ceases therefore to be only connected with coordinating various activities and to guarantee proper movement, but is extended by the elements optimizing the production level of inventories in the course of production. This article presents an example of a company that has faced such a challenge. A comparative study has been carried out of the various types of planning, which has led to attempting to use an optimization model to minimize the inventory and the production costs for one of the departments that has been studied
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 177-191
Keywords: optymalizacja; produkcja; planowanie produkcji; optimalization; production; production planning